Analysis of Thermal Synergy and Thermal Overlapping in Multifocal Breast Tumor Hyperthermia Therapy - Roseman, Nur Amani Hanis; Ishkrizat Taib, (Journal of Advanced Mechanical Engineering Applications, 2026)
Hyperthermia is a promising complementary treatment which improves the therapeutic efficacy of conventional cancer therapies by utilizing controlled elevation of tumor temperature. Although numerous studies have investigated temperature distribution in individual breast tumor, the behavior of thermal interaction between multiple tumor regions remains inadequately quantified. This study presents a secondary analysis of previously obtained computational fluid dynamics (CFD) simulation data to assess thermal interaction in single and triple clustered breast tumor configurations exposed to hyperthermia treatment. Temperature profiles were extracted and analyzed for tumor diameters of 2 and 4 cm under 40°C, 45°C and 50°C heating conditions. Three quantitative metrics were evaluated including thermal overlap, inter-tumor thermal variation (?T) and thermal synergy index (TSI). The findings demonstrate that clustered tumors constantly exhibited bigger thermally affected regions in comparison to equivalent single tumor configurations. This may indicate stronger spatial interaction of thermal regions. Nevertheless, clustering also increased temperature heterogeneity with ?T values rising from 4.72°C to 15.26°C and 7.60°C to 16.43°C as heating condition elevated from 40°C to 50°C in 2 and 4 cm tumors’ cluster respectively. Thermal synergy analysis displayed a temperature dependent behavior as TSI value increased from 0.991 at 40°C to 1.018 for 2 cm tumors and consistent positive synergy for 4 cm tumor reaching a maximum TSI value of 1.021 at 50°C. Findings observed in this study reveal that clustering tumor increase conductive thermal interaction as well as promotes synergy heat buildup at high temperatures but accompanied by a reduction in thermal uniformity. Therefore, this study provides a quantitative framework to evaluate thermal interaction involving multifocal breast tumor. It also offers supplementary insight into the influence of heating intensity and tumor size on hyperthermia treatment performance.